Little-Known Indications of Musical Performance from the Fifteenth Century and Their Historical Context - Kujumdzieva, Svetlana (Journal of the International Society for Orthodox Music, 2020)
The period of the fourteenth and fifteenth centuries is extremely rich in the compilation of different traditions in the field of Balkan Orthodox music. One of the reasons for that might be attributed to the spread of the revised liturgical ordo of Jerusalem. Along with this ordo came the revival of hesychasm, a movement for spiritual renewal. The aim was the unity of Orthodoxy, to be fostered at a time when the common fear of Islamic invasion in the Balkans increased. There was a search for both the accommodation of sacred texts to the revised liturgical ordo and the reestablishment of the authenticity of sacred texts that had been lost in the preceding century during the Latin occupation. The hesychasts believed that God could be reached through pure devotion. They paid special attention to the word. The word became a means of expression to reach God. Its “divine beauty” was sought. The style of “плетение словес”(“weaving of words”) was developed, and work focused on “исправление книг” (“the correction of books”). The performance of the musical pieces in the church became very important. Respectively, the role of church singers increased greatly. It is not by chance that their pictures appear just at that time in both frescos in churches and on the pages of manuscripts. Of great interest are the unique musical indications on the margin of an old Glagolitic fragment from the eleventh century, which was found in the inside cover of a manuscript from the 15th century. The performance term “тресене” (“quiver in the throat”) predominates in them: “quiver slowly in the throat”, “quiver faster in the throat”, “with quiver”, etc. Who the writer of these indications was and where they were written are questions for discussion.